EU regional policy: Its theoretical foundations and their policy conclusions revisited - Peter Schmidt (European Regional Science Association (ERSA), 2014)
This paper reconsiders the theoretical foundations of EU regional policy in economics. It begins with a discussion of the line of thought of its prevalent explanation in equilibrium economics which is focusing on market failures as its key underpinning and which is the major toolkit of economists for policy recommendations in this context. Subsequently, this view is contrasted with a non-equilibrium economics perspective on EU regional policy. Based on this, the existence of market failures and the relevance of equilibrium economics for a realistic understanding of and policy advice for EU regional policy are called into question. That is why, a more substantive politico-economic explanation and different policy conclusions for the regional policy of the EU are offered. The paper particularly focuses on the implications of the latter for the European Economic and Monetary Union in light of the persisting financial crisis and the vast economic disparities existing within it. Finally, the non-equilibrium economics perspective on EU regional policy is also animadverted, since market failure thinking still prevails in this branch of economics undermining its own criticism of equilibrium economics.
Keywords: B52; E62; F12; H53; O10; R00; 330; circular and cumulative causation; structural funds; non-equilibrium economics; increasing returns; EU regional policy; market failures